Anticipation and Instability of IT-15 (CAG)N Repeats in Parent-Offspring Pairs with Huntington Disease - Ranen, Neal G. (1995)
Huntington disease (HD) is an autosomal dominant degenerative disorder caused by an expanded and unstable trinucleotide repeat (CAG)n in a gene (IT-15) on chromosome 4. HD exhibits genetic anticipation—earlier onset in successive generations within a pedigree. From a population-based clinical sample, we ascertained parent-offspring pairs with expanded alleles, to examine the intergenerational behavior of the trinucleotide repeat and its relationship to anticipation. We find that the change in repeat length with paternal transmission is significantly correlated with the change in age at onset between the father and offspring. When expanded triplet repeats of affected parents are separated by median repeat length, we find that the longer paternal and maternal repeats are both more unstable on transmission. However, unlike in paternal transmission, in which longer expanded repeats display greater net expansion than do shorter expanded repeats, in maternal transmission there is no mean change in repeat length for either longer or shorter expanded repeats. We also confirmed the inverse relationship between repeat length and age at onset, the higher frequency of juvenile-onset cases arising from paternal transmission, anticipation as a phenomenon of paternal transmission, and greater expansion of the trinucleotide repeat with paternal transmission. Stepwise multiple regression indicates that, in addition to repeat length of offspring, age at onset of affected parent and sex of affected parent contribute significantly to the variance in age at onset of the offspring. Thus, in addition to triplet repeat length, other factors, which could act as environmental factors, genetic factors, or both, contribute to age at onset. Our data establish that further expansion of paternal repeats within the affected range provides a biological basis of anticipation in HD.